2014
DOI: 10.22495/cocv12i1c9p1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of corporate social responsibility on firm performance: Evidence form a MENA country

Abstract: This paper investigates the effect of corporate social responsibility (CSR) on organization performance. It uses cross sectional data from non-financial companies in Egypt that derived from the Kompass Egypt data base. Regression analysis was used to explain the relationship and the effect of CSR on organization financial performance. The findings of this study found that there is a positive and significant effect of CSR on firm performance. Also, all CSR dimensions have significant relationship with firm fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…They interpret the connection between these 2 variables from the perspective of legitimacy, agency, stakeholders' and singling theory base on the previous studies. Basuony et al (2014) investigated the CSR influence on FP. The result showed that there is a significantly positive influence on CSR on company performance by using cross-sectional data.…”
Section: Studies Regarding the Association Between Em And Csrmentioning
confidence: 99%
“…They interpret the connection between these 2 variables from the perspective of legitimacy, agency, stakeholders' and singling theory base on the previous studies. Basuony et al (2014) investigated the CSR influence on FP. The result showed that there is a significantly positive influence on CSR on company performance by using cross-sectional data.…”
Section: Studies Regarding the Association Between Em And Csrmentioning
confidence: 99%
“…Most of the authors indicated that there are strong relationships between CSR dimensions and company's financial performance (Mishra and Suar, 2010;Sahin et al, 2011;Wang and Zhang, 2012;Belascu and Horobet, 2013;Heydarian et al, 2013;Mwangi and Jerotich, 2013;Bidhari et al, 2013;Basuony et al, 2014;Murtaza et al, 2014;Ding, 2014;Mujahid and Abdullah, 2014;Rahmawati et al, 2014;Mumtaz and Pirzada, 2014;Dzhavdatovna et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Firms worldwide are becoming more adoptive of the concept of being socially responsible entities and are increasingly working on integrating the strategies and practices of responsibility into the core of their practices. In addition to this, companies are being more alert to the impact of their CSR practices and communication (Akisik and Gal, 2011; Klettner et al , 2014; Basuony et al , 2014a). CSR communication and reporting is expected to reduce the information asymmetry and improve the companies’ relations with their stakeholders (Gul and Leung, 2004).…”
Section: Introductionmentioning
confidence: 99%